2021
DOI: 10.18070/erciyesiibd.871710
|View full text |Cite
|
Sign up to set email alerts
|

Does the Aging Population Become a Constraint to the Growth of Turkish Economy? New Evidence from Time Series Analysis

Abstract: This study deals with the relationship between population aging and economic growth in Turkey during 1970-2018 and includes domestic savings, consumption expenditures, and financial development in the growth specification as additional variables. The Johansen and ARDL bounds test for cointegration analysis were used. Moreover, DOLS and CCR estimators were used to estimate the long-run coefficients. The VECM causality procedure was employed for causality analysis. The findings revealed that the variables are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Hence, the countries need to increase labor force growth rate to balance decline in economic growth caused by ageing population. In a study of Turkey, Ecevit et al (2021) discovered that population aging, and financial development had a negative impact on economic growth, whereas domestic savings and consumption expenditures were positively related to economic growth in the long run. The findings also showed that in the long run, there is bidirectional causality between all the independent variables and economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, the countries need to increase labor force growth rate to balance decline in economic growth caused by ageing population. In a study of Turkey, Ecevit et al (2021) discovered that population aging, and financial development had a negative impact on economic growth, whereas domestic savings and consumption expenditures were positively related to economic growth in the long run. The findings also showed that in the long run, there is bidirectional causality between all the independent variables and economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%